The Emergence of bla-CTX-M and bla-TEM in ESBL Producing Klebsiella pneumoniae in Aquaculture in Southeast Asia: A Systematic Review - Alfonso, Argelyn Faye M.; Jesus, Reina Therese R. De; Dyquiangco, Allen Christian M.; Guides, Niña Mae G.; Nocasa, Silver Jae Nicole U.; Peralta, Glopearl Stephan S.; Santiago, Gabriel Eli A.; Sarmiento, Monica Mae A.; Tolenada, Charlene Princess S. (Asian Journal of Biological and Life Sciences)
ESBL Klebsiella pneumoniae contributes widely to the alarming increase observed globally in antibiotic resistance within the past few years. The aquaculture sector is known as a fast-emerging business today. It is one of the significant concerning sectors with the emerging ESBL-producing K. pneumoniae due to its complex treatment and easy-transfer genes. This mini-review aims to determine the emergence of bla-CTX-M and bla-TEM genes in ESBL-producing K. pneumoniae found in aquaculture within Southeast Asia. All qualified journals considered have been conscientiously examined and passed the mini-review criteria; 8 eligible studies from Southeast Asia from 2016 to 2021 were utilized. Among the eight journals, five out of the eight studies have displayed the detection of the bla-CTX-M gene found within freshwater, fish markets, and integrated farming systems in Thailand and India, with a prevalence of 44.38% and 33.73%, respectively. The remaining three studies display bla-TEM genes found in freshwater, retail markets, and freshwater aquaculture in Hongkong and the Philippines, with a prevalence of 19.53% and 2.37%. Within Southeast Asia, 37.50% account for the bla-TEM gene, while 62.50% account for bla-CTX-M, making it the most pervasive gene found within Southeast Asia. Infections caused by ESBL-producing K. pneumoniae can be resistant to various antibiotics, complicating the treatment process. Observing proper hygiene and taking extra precautions can significantly reduce ESBL-producing K. pneumoniae emergence.
Keywords: Aquaculture; bla-CTX-M; bla-TEM; Extended-spectrum-beta-lactamase-producing Klebsiella pneumoniae